2016
DOI: 10.7554/elife.12411
|View full text |Cite|
|
Sign up to set email alerts
|

The Sec7 N-terminal regulatory domains facilitate membrane-proximal activation of the Arf1 GTPase

Abstract: The Golgi complex is the central sorting compartment of eukaryotic cells. Arf guanine nucleotide exchange factors (Arf-GEFs) regulate virtually all traffic through the Golgi by activating Arf GTPase trafficking pathways. The Golgi Arf-GEFs contain multiple autoregulatory domains, but the precise mechanisms underlying their function remain largely undefined. We report a crystal structure revealing that the N-terminal DCB and HUS regulatory domains of the Arf-GEF Sec7 form a single structural unit. We demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 55 publications
2
42
0
Order By: Relevance
“…37 The DCB and HUS domains of yeast Sec7 form a compact helical structure in which the conserved HUS motif is unstructured and they have no structural resemblance to known membrane-binding domains. 38 We demonstrate here that the DCB-HUS tandem is a membrane-binding element and that it contributes to the efficiency of Arf activation. A purified human BIG1 construct spanning the DCB-HUS-Sec7 domains associated directly with membranes in a liposome co-sedimentation assay (Fig.…”
Section: Regulation Of Large Arfgefs By Direct and Small Gtpase-mediamentioning
confidence: 99%
See 1 more Smart Citation
“…37 The DCB and HUS domains of yeast Sec7 form a compact helical structure in which the conserved HUS motif is unstructured and they have no structural resemblance to known membrane-binding domains. 38 We demonstrate here that the DCB-HUS tandem is a membrane-binding element and that it contributes to the efficiency of Arf activation. A purified human BIG1 construct spanning the DCB-HUS-Sec7 domains associated directly with membranes in a liposome co-sedimentation assay (Fig.…”
Section: Regulation Of Large Arfgefs By Direct and Small Gtpase-mediamentioning
confidence: 99%
“…40 In a contrasting set of experiments, a yeast Sec7 construct carrying the DCB-HUS-Sec7 domains did not bind to membranes autonomously and was 3-4-fold less active on membranes than in solution. 38,41 This construct was however about 4-fold more active on membranes than the Sec7 domain and this led to a model in which it was proposed to assist in the displacement of the N-terminal helix of Arf. 38 Together, these studies point to a conserved function of the DCB-HUS domains in the association of large ArfGEFs with membranes and in the regulation of their activity, possibly with different structural implementations between subfamilies and/or species that remain to be established.…”
Section: Regulation Of Large Arfgefs By Direct and Small Gtpase-mediamentioning
confidence: 99%
“…We observed that Cex1 co-localizes with endosomes stained with FM4-64 but not with the vacuolar membrane. To determine whether Cex1 is also localized at the trans-Golgi network (TGN) as the COPIb subcomplex (Gabriely et al, 2007), we co-transformed the yeast cells with the Sec7-DsRed TGN-localized yeast protein (Richardson et al, 2016). Our microscopy observations show that Cex1 partially co-localized with the Sec7-DsRed punctuated structures present in the cells, both in fermentation and respiration ( Fig 4G).…”
Section: Intracellular Localization Of Cex1mentioning
confidence: 72%
“…Characteristics of ARFGEF2 mutations and related protein domains, including the mutation presented in this study (Table 1). Previous studies have focused on the Sec7 domain, which acts on the surface of membranes to insert another regulatory protein (called Arf1) into the membranes of the Golgi complex [31,32]. Hence, it is necessary to reconsider the importance of the Armadillo-type fold domain.…”
Section: Discussionmentioning
confidence: 99%